THE JURASSIC-CRETACEOUS TRANSITION IN WEST-CENTRAL ARGENTINA: NEW BIOSTRATIGRAPHIC DATA FOR ITS DEFINITION - Verónica V. Vennari; Marina A. Lescano; Luciana S. Marin; Beatriz Aguirre-Urreta; Damian G. Lodowski; Pierre Pellenard; Mathieu Martinez (Cretaceous Research, 2026)

Strengthening biodiversity conservation and One Health through ranger monitoring of wildlife health in protected areas - Diego Montecino‐Latorre; Sarah H. Olson; Emily Denstedt; Luis Guerra; Paulo Colchao‐Claux; Lucy Keatts; Aristide Andrianarimisa; Lovasoa Rabarisoa; Manfredo Martínez; Sophalrachana Kong; Devin Vorn; Zeveyda Jhancy Segura; et al. (Conservation Biology, 2026)
The lack of wildlife health (WH) surveillance systems leaves critical gaps in biodiversity conservation and One Health protection. Integrating rangers patrolling protected areas (PAs) into WH monitoring represents a cost‐effective and scalable opportunity to address these gaps at key human–wildlife interfaces and nature strongholds. For the past 2.5 years, organizations across 4 countries have collaborated to pilot this integration. The approach involved establishing a practical definition of health event for rangers patrolling PAs, developing a referential form tailored for rangers to document these events, training key country actors to identify and record health events on this form, merging this form with local forms used by rangers to record other events of interest observed during their patrols (e.g., illegal logging), and training rangers to identify and document health events with the modified local form. We examined 4 case studies involving dozens of PAs in different countries with different languages and local partners. The recording of health events was supported by the Spatial Monitoring And Reporting Tool, SMART, which provides the modified form for rangers on mobile devices and enabled standardized recording of events. Currently, over 200 rangers across more than 50 PAs have been trained, and more than 1000 health events have been recorded. This provides early evidence that rangers could enhance WH monitoring and strengthen biodiversity conservation, ultimately fostering One Health. This initiative lays important groundwork for overcoming key barriers (e.g., lack of personnel and funding) to establishing functional WH surveillance systems in PAs. Still, specific data infrastructure, human resources, and institutional support are needed. It will be important to evaluate the limitations of ranger‐collected data and align monitoring goals with the capabilities of rangers and data managers. Expansion to additional PAs is planned, alongside efforts to integrate ranger‐collected data into multisectoral One Health frameworks.

Polyselenylsulfides as neglected central intermediates in Selenium cycling - Mathieu Martinez; Markus Lenz (Chemosphere, 2026)

New dating results at Incarcal‐I (Spain) shed light on the exceptionally rich late Early Pleistocene fossil record of the Iberian Peninsula - Mathieu Duval; Oriol Oms; Bienvenido Martinez‐Navarro; Rainer Grün; Isaac Rufí; María Prat‐Vericat; Sergio Ros‐Montoya; Maria Patrocinio Espigares; Joan Madurell‐Malapeira (Journal of Quaternary Science, 2026)
More than five decades after the first report of fossil remains found in a limestone quarry near Crespià, NE Spain, we provide here the first dating results for the palaeontological assemblage from Incarcal‐I, one of the various fossil‐rich sinkholes identified at the locality that has yielded ~2,000 remains representing at least 15 taxa of large mammals. Palaeomagnetism in conjunction with combined U‐series and electron spin resonance (ESR) dating of fossil teeth consistently constrain the age of Incarcal‐I to the latest part of the Early Pleistocene. Specifically, with palaeomagnetic results showing reverse magnetic polarities for the large majority of the samples and no indisputable evidence of normal polarity in the stratigraphic succession, the deposits may be reasonably correlated to the Matuyama Chron (2.61–0.77 Ma), thus providing a minimum age constraint of 0.77 Ma for the sedimentary infill. Additionally, direct dating of two fossil teeth of Hippopotamus antiquus using the most advanced analytical procedures, through a combination of unusually high sampling density ( n = 17) for bulk ESR and U‐series analyses and high‐resolution laser ablation Inductively Coupled Plasma‐Mass Spectrometry (ICP‐MS) analyses, yields a mean age of 862 ± 52 ka (1σ). Interestingly, the data set collected shows the exceptionally high spatial homogeneity of the ESR and U‐series data across dental tissues and of the natural radioactivity of the sedimentary environment. Furthermore, the uncertainty around the uranium uptake modelling carries very little weight in the age calculation, which is unusual for such old fossil teeth. Consequently, this set of evidence supports the robustness and reliability of the ESR chronology, adding a new solid chronological tie point for biochronological inferences. In summary, the various lines of evidence available enable confident positioning of Incarcal‐I in the latest part of the Early Pleistocene, that is, somewhere between the end of the Jaramillo Subchron (1.01 Ma) and the Matuyama–Brunhes boundary (0.77 Ma). The numerical dating results indicate that the fossil assemblage of Incarcal‐I is coeval with those from other well‐constrained key Spanish localities such as Atapuerca Gran Dolina TD4‐6, and Vallparadís Station EVT7, highlighting the overall exceptional density of the Iberian fossil record between ~0.8 and ~1.0 Ma. Finally, a critical evaluation of the existing age constraints available for the Calabrian (1.80–0.77 Ma) fossil localities of the Iberian Peninsula is also proposed here, with a first tentative classification of the sites into four main categories (A to D) based on the robustness and precision of their chronostratigraphic framework.

Climate changes at the Jurassic/Cretaceous transition vs. supra-regional oceanographic processes: Insights from the Vocontian Basin (Clue de Taulanne section, SE France) - Damian Gerard Lodowski; Johann Schnyder; Justyna Kowal-Kasprzyk; Jean-François Deconinck; Mathieu Martinez; Andrzej Chmielewski; Izabela Ploch; Jacek Grabowski (Global and Planetary Change, 2025)

Spatial biases in oxygen-based Phanerozoic seawater temperature reconstructions - Alexandre POHL; Thomas W. WONG HEARING; Arnaud BRAYARD; Ethan GROSSMAN; Michael M. JOACHIMSKI; Guillaume LE HIR; Thomas LETULLE; Daniel J. LUNT; Mathieu MARTINEZ; Emmanuelle PUCEAT; Guillaume SUAN; Paul VALDES; et al. (Earth and Planetary Science Letters, 2025)

Organic-walled dinoflagellate cyst record across the Campanian–Maastrichtian (Upper Cretaceous) boundary stratotype section (Tercis-les-Bains, SW France) - Mariusz Niechwedowicz; Silke Voigt; Delphine Desmares; Agata Jurkowska; Mathieu Martinez (Marine and Petroleum Geology, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

Environmental selenium volatilization is possibly conferred by promiscuous reactions of the sulfur metabolism - Ying Liu; Andreas Schäffer; Mathieu Martinez; Markus Lenz (Chemosphere, 2023)

Upper Jurassic (Tithonian) belemnites from the Neuquén Basin, Argentina - Verónica V. Vennari; Beatriz Aguirre-Urreta; Luciana S. Marin; Pierre Pellenard; Mathieu Martinez; Maisa Tunik (Journal of South American Earth Sciences, 2023)

Synchrony of carbon cycle fluctuations, volcanism and orbital forcing during the Early Cretaceous - Mathieu Martinez; Beatriz Aguirre-Urreta; Guillaume Dera; Marina Lescano; Julieta Omarini; Maisa Tunik; Luis O'Dogherty; Roque Aguado; Miguel Company; Stéphane Bodin (Earth-Science Reviews, 2023)

In vivo exposure of marine mussels to venlafaxine: bioconcentration and metabolization - Elena Gomez; Clothilde Boillot; Maria Jesus Martinez Bueno; Dominique Munaron; Olivier Mathieu; Frédérique Courant; Hélène Fenet (Environmental Science and Pollution Research, 2021)

Nurses’ internal contamination by antineoplastic drugs in hospital centers: a cross-sectional descriptive study - Antoine Villa; Mathieu Molimard; Dunia Sakr; Régis Lassalle; Emmanuelle Bignon; Béatrice Martinez; Magali Rouyer; Simone Mathoulin-Pelissier; Isabelle Baldi; Catherine Verdun-Esquer; Mireille Canal-Raffin (International Archives of Occupational and Environmental Health, 2021)

Growth and resilience responses of Scots pine to extreme droughts across Europe depend on predrought growth conditions - Arun K. Bose; Arthur Gessler; Andreas Bolte; Alessandra Bottero; Allan Buras; Maxime Cailleret; J. Julio Camarero; Matthias Haeni; Ana‐Maria Hereş; Andrea Hevia; Mathieu Lévesque; Juan C. Linares; et al. (Global Change Biology, 2020)
Global climate change is expected to further raise the frequency and severity of extreme events, such as droughts. The effects of extreme droughts on trees are difficult to disentangle given the inherent complexity of drought events (frequency, severity, duration, and timing during the growing season). Besides, drought effects might be modulated by trees’ phenotypic variability, which is, in turn, affected by long‐term local selective pressures and management legacies. Here we investigated the magnitude and the temporal changes of tree‐level resilience (i.e., resistance, recovery, and resilience) to extreme droughts. Moreover, we assessed the tree‐, site‐, and drought‐related factors and their interactions driving the tree‐level resilience to extreme droughts. We used a tree‐ring network of the widely distributed Scots pine ( Pinus sylvestris ) along a 2,800 km latitudinal gradient from southern Spain to northern Germany. We found that the resilience to extreme drought decreased in mid‐elevation and low productivity sites from 1980–1999 to 2000–2011 likely due to more frequent and severe droughts in the later period. Our study showed that the impact of drought on tree‐level resilience was not dependent on its latitudinal location, but rather on the type of sites trees were growing at and on their growth performances (i.e., magnitude and variability of growth) during the predrought period. We found significant interactive effects between drought duration and tree growth prior to drought, suggesting that Scots pine trees with higher magnitude and variability of growth in the long term are more vulnerable to long and severe droughts. Moreover, our results indicate that Scots pine trees that experienced more frequent droughts over the long‐term were less resistant to extreme droughts. We, therefore, conclude that the physiological resilience to extreme droughts might be constrained by their growth prior to drought, and that more frequent and longer drought periods may overstrain their potential for acclimation.

A genomic map of climate adaptation in Mediterranean cattle breeds - Laurence Flori; Katayoun Moazami‐Goudarzi; Véronique Alary; Abdelillah Araba; Ismaïl Boujenane; Nadjet Boushaba; François Casabianca; Sara Casu; Roberta Ciampolini; Armelle Coeur D'Acier; Corinne Coquelle; Juan‐Vicente Delgado; et al. (Molecular Ecology, 2019)
Domestic species such as cattle ( Bos taurus taurus and B. t. indicus ) represent attractive biological models to characterize the genetic basis of short‐term evolutionary response to climate pressure induced by their post‐domestication history. Here, using newly generated dense SNP genotyping data, we assessed the structuring of genetic diversity of 21 autochtonous cattle breeds from the whole Mediterranean basin and performed genome‐wide association analyses with covariables discriminating the different Mediterranean climate subtypes. This provided insights into both the demographic and adaptive histories of Mediterranean cattle. In particular, a detailed functional annotation of genes surrounding variants associated with climate variations highlighted several biological functions involved in Mediterranean climate adaptation such as thermotolerance, UV protection, pathogen resistance or metabolism with strong candidate genes identified (e.g., NDUFB3 , FBN1 , METTL3 , LEF1 , ANTXR2 and TCF7 ). Accordingly, our results suggest that main selective pressures affecting cattle in Mediterranean area may have been related to variation in heat and UV exposure, in food resources availability and in exposure to pathogens, such as anthrax bacteria ( Bacillus anthracis ). Furthermore, the observed contribution of the three main bovine ancestries (indicine, European and African taurine) in these different populations suggested that adaptation to local climate conditions may have either relied on standing genomic variation of taurine origin, or adaptive introgression from indicine origin, depending on the local breed origins. Taken together, our results highlight the genetic uniqueness of local Mediterranean cattle breeds and strongly support conservation of these populations.

Over-sulfated glycosaminoglycans are alternative selectin ligands: insights into molecular interactions and possible role in breast cancer metastasis - Pierre Martinez; Gérard Vergoten; Florent Colomb; Marie Bobowski; Agata Steenackers; Mathieu Carpentier; Fabrice Allain; Philippe Delannoy; Sylvain Julien (Clinical & Experimental Metastasis, 2013)